2017
DOI: 10.1007/s00192-017-3518-x
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable transobturator sling for the treatment of primary stress urinary incontinence

Abstract: The adjustable transobturator sling minimizes the risk of postoperative voiding dysfunction and allows high objective and subjective cure rates to be achieved in patients with primary SUI. The technique also improves the patient's quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
7
0
3
Order By: Relevance
“…It should be noted that the above‐described systems were used mostly in patients with more complex SUI (hypomobile urethra, Intrinsic urethral sphincter deficiency, etc.). At the same time, patients with standard SUI underwent considerable amount of adjustments as well 9 . Within our study, 43.6% patients required tension adjustment.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…It should be noted that the above‐described systems were used mostly in patients with more complex SUI (hypomobile urethra, Intrinsic urethral sphincter deficiency, etc.). At the same time, patients with standard SUI underwent considerable amount of adjustments as well 9 . Within our study, 43.6% patients required tension adjustment.…”
Section: Discussionmentioning
confidence: 50%
“…According to the studies, adjustment frequency ranged between 27.3% and 46.8% and short-term effectiveness was 84.4%-93.7%. 9,[13][14][15][16] It should be noted that the abovedescribed systems were used mostly in patients with more complex SUI (hypomobile urethra, Intrinsic urethral sphincter deficiency, etc.). At the same time, patients with standard SUI underwent considerable amount of adjustments as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Shkarupa et al, the UDI-6, IIQ-7 and ICIQ-SF scores at 12 months after TOT treatment were found to be significantly decreased compared to the preoperative values. 19 In a follow-up of 78 patients for an average of 13.5 months after TOT surgery, Huang et al reported a significant decrease in the postoperative UDI-6 and IIQ-7 scores compared to the preoperative values. 20 In our study, the postoperative IIQ-7, UDI-6 and ICIQ-SF scores were also significantly lower than the preoperative values.…”
Section: Discussionmentioning
confidence: 98%